(untitled) (Hematology Meeting Reports, 2009)
Over the past few years the inherited disorders of erythrocyte metabolism have been the object of intensive research which has resulted in a better understanding of their molecular basis. Many genes encoding for red cell enzymes of various metabolic pathways have been cloned and numerous mutations identified. More recently, the comparison of the recombinant mutants with the wild-type enzymes has enabled the effects of amino acid replacements on the enzyme molecular properties to be determined and help to correlate genotype to clinical phenotype. However, the clinical manifestations of red cell enzyme defects are not merely dependent on the molecular properties of the mutant protein but rather reflect the complex interactions of additional factors, including genetic background, concomitant functional polymorphisms of other enzymes, posttranslational or epigenetic modifications, ineffective erythropoiesis and differences in splenic function.